Penentu-penentu ketidakpatuhan cukai di kalangan Syarikat Kecil dan Sederhana di Malaysia: Data Audit Cukai LHDNM - Wan Pariza, Wan Omar (2018)
Tax is an important economics resources for the development of a country. In Malaysia, income tax is a direct tax that is under the jurisdiction of the Inland Revenue Board of Malaysia (IRBM) and it is a major contributor to most national income. Even though the tax collected by the IRBM increases annually, the problem of non-compliance also increases with the increasing number of tax audit cases finalized with audit adjustments and penalties. This study was conducted to identify the significant differences between the factors of tax non-compliance among Small and Medium Corporations (SMCs).The focus of the study is on the four factors that determine the tax non-compliance of the SMCs which is industry type, company location, company size and company's financial liquidity. This study is a quantitative study using secondary data obtained from the IRBM Case Management System. Population sample of this study are SMCs tax audit cases finalized in year 2015 at all IRBM branches. The findings show that there is a significant difference in SMCs tax non-compliance between the sizes of the company. However there is no significant difference in SMCs tax non-compliance between the industry type, company location and financial liquidity of the company. Research findings hopefully will be a value added to the tax literatures and thus help the tax authorities to enhance the tax compliance strategy among SMCs.